Songs, Stories and Sisterhood: The Rasengs as Indigenous Institutions of Women’s Learning Among the Adis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The Rasengs of the Adis of Upper Siang in Arunachal Prdesh were once vibrant social and educational institutions that nurtured young girls in discipline, art, responsibility and collective memory. These served as dormitories for unmarried women and acted as the indigenous schools of life where knowledge, skills and traditions were transmitted orally through songs, stories and community living. This paper explores the Raseng system as an institution of indigenous institution of women’s learning, empowerment, sisterhood and socialisation. Drawing from historical accounts and personal interviews, it argues that the Rasengs embodied an indigenous feminist pedagogy that integrated moral, aesthetic and practical education long before formal education reached the Adi villages.